2017
DOI: 10.1007/s00521-017-3066-9
|View full text |Cite
|
Sign up to set email alerts
|

Recursive least-squares temporal difference learning for adaptive traffic signal control at intersection

Abstract: This paper presents a new method to solve the scheduling problem of adaptive traffic signal control at intersection. The method involves recursive least-squares temporal difference (RLS-TD(λ))learning that is integrated into approximate dynamic programming. The learning mechanism of RLS-TD(λ) is to make an adaptation of linear function approximation by updating its parameters based on environmental feedback. This study investigates the method implementation after modelling a traffic dynamic system at intersect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The training parameters of the proposed algorithm are tuned after repeating the experiment in reason to attempt the best score value in Equation 17and the minimum RMSE using Equation 18for the test set in both Equations (17) and (18).…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The training parameters of the proposed algorithm are tuned after repeating the experiment in reason to attempt the best score value in Equation 17and the minimum RMSE using Equation 18for the test set in both Equations (17) and (18).…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…After the training model is initialized, the USS-based TD objective function is proposed to adopt the RLS weights to the new data variations [18]. Furthermore, we proposed, based on [8,18,26], a new DFF formula that is proposed as illustrated in Equation 10, so Equations (4) and (5) will be changed, respectively, into (9) and (10).…”
Section: Proposed Os-elmmentioning
confidence: 99%
See 1 more Smart Citation
“…Each traffic control technique was evaluated using the SUMO simulator, and the result showed that ATOM is efficient during road conditions with high congestion. Publication written by Yin et al [41] analyses adaptive traffic light applied to a single two‐lane intersection environment. The experiment analysed which of five control schemes fits best for such a problem.…”
Section: Literature Analysismentioning
confidence: 99%
“…Some methodologies for estimating model parameters have been proposed using the RLS method, which updates a vector of parameters and has a lower computational cost than the method of non-recursive least squares [5]. Many researches were developed looking for an improvement of the RLS using other algorithms like neural networks, fuzzy systems, network based fuzzy inference system (ANFIS) and metaheuristics [23]- [29].…”
Section: Introductionmentioning
confidence: 99%